INSTAGRAM TO LEARN ENGLISH VOCABULARY: A STUDY OF INDONESIAN NON-ENGLISH MAJOR UNIVERSITY STUDENTS - Thesalonika Dwi Wardhani Puspita Baruti; Adaninggar Septi Subekti (IJEE (Indonesian Journal of English Education), 2023)
ABSTRACTThis study aimed to investigate the attitudes of non-English primary university students in Indonesia on using Instagram for vocabulary learning and to find out the students' views of learning English vocabulary using Instagram. Considering the popularity of Instagram among Indonesian university students and the scarcity of such studies involving non-English primary students, investigating their use of Instagram for English vocabulary learning can be worthwhile and relevant. The study involved 213 student participants who were Instagram users in an online survey and six in online interviews. The survey found that the participants generally had positive attitudes toward using Instagram for vocabulary learning. However, the study found the participants' somewhat ambivalent views through the Thematic Analysis of the interview data. Students reported consciously learning new isolated English vocabulary from English captions on Instagram. They unconsciously acquired isolated English vocabulary from photos and videos on Instagram. However, Instagram was not helping in obtaining vocabulary in contexts as it gave a limited content explanation. The findings could help teachers to make an informed decision when using Instagram in the instructional process, optimizing its strength and potential.ABSTRAKTujuan studi ini adalah untuk mengetahui sikap mahasiswa jurusan non-bahasa Inggris di Indonesia terhadap penggunaan Instagram untuk pembelajaran kosakata bahasa Inggris dan untuk mengetahui pandangan mahasiswa mengenai pembelajaran kosakata bahasa Inggris menggunakan Instagram. Mengingat bahwa kepopuleran Instagram di kalangan mahasiswa dan bahwa studi yang melibatkan mahasiswa jurusan non-bahasa Inggris masih cukup langka, studi yang melibatkan kelompok mahasiswa ini sangat diperlukan dan relevan. Studi melibatkan 213 mahasiswa pengguna Instagram melalui survei daring dan enam diantaranya melalui wawancara daring. Studi ini menemukan bahwa para peserta secara umum memiliki sikap positif terhadap penggunaan Instagram untuk pembelajaran kosakata. Namun, melalui analisis tematik hasil wawancara, ditemukan bahwa peserta wawancara memiliki pandangan yang sedikit ambivalen. Mereka melaporkan bahwa melalui Instagram, mereka secara sadar mempelajari kosakata lepas baru melalui captions Instagram. Selanjutnya, para peserta melaporkan bahwa secara tidak sadar mereka memperoleh kosakata lepas dari foto dan video di Instagram. Namun, dilaporkan bahwa Instagram tidak begitu membantu dalam pemerolehan kosakata dalam konteks. Hasil studi ini dapat membantu pengajar untuk membuat keputusan yang tepat saat menggunakan Instagram dalam proses pembelajaran, mengoptimalkan kekuatan dan potensinya.How to Cite: Baruti, T.D.W.P., Subekti, A.S. (2023). Instagram to Learn English Vocabulary: A Study of Indonesian Non-English Major University Students. IJEE (Indonesian Journal of English Education), 10(1), 106-125. doi:10.15408/ijee.v10i1.26969